Characterizing nuclear morphology and expression of eNOS in vascular endothelial cells subjected to a continuous range of wall shear stress magnitudes and directionality. (January 2023) - Sahni, Jaideep; Arshad, Mehwish; Schake, Morgan A.; Brooks, Justin R.; Yang, Ruiguo; Weinberg, Peter D.; Pedrigi, Ryan M.
Abstract: Complex patterns of hemodynamic wall shear stress occur in regions of arterial branching and curvature. Areas within these regions can be highly susceptible to atherosclerosis. Although many studies have characterized the response of vascular endothelial cells to shear stress in a categorical manner, our study herein addresses the need of characterizing endothelial behaviors over a continuous range of shear stress conditions that reflect the extensive variations seen in the vasculature. We evaluated the response of human umbilical vein endothelial cell monolayers to orbital flow at 120, 250, and 350 revolutions per minute (RPM) for 24 and 72 h. The orbital shaker model uniquely provides a continuous range of shear stress conditions from low and multidirectional at the center of each well of a culture plate to high and unidirectional at the periphery. We found distinct patterns of endothelial nuclear area, nuclear major and minor diameters, nuclear aspect ratio, and expression of endothelial nitric oxide synthase over this range of shear conditions and relationships were fit with linear and, where appropriate, power functions. Nuclear area was particularly sensitive with increases in the low and multidirectional WSS region that incrementally decreased as WSS became higher in magnitude and more unidirectional over the radius of the cell layers. The patterns of all endothelial behaviors exhibited high correlations (positive and negative) with metrics of shear stress magnitude and directionality that have been shown to strongly associate with atherosclerosis. Our findings demonstrate the exquisite sensitivity of these endothelial behaviors to incremental changes in shear stress magnitude and directionality, and provide critical quantitation of these relationships for predicting the susceptibility of an arterial segment to diseases such as atherosclerosis, particularly within complex flow environments in the vasculature such as around bifurcations. Graphical abstract: Image 1 Highlights: Vascular endothelial cells are subjected to a range of shear stress conditions. The orbital shaker model captures physiologic shear magnitudes and directionality. Nuclear morphology is particularly sensitive to incremental changes in shear stress. Nuclear morphology and eNOS exhibit strong correlations with shear stress metrics. These data are important for predicting endothelial and arterial functions.